The application of in situ AFM to the study of molecular and macromolecular crystallization - Keel, Trevor (2004)
The crystallization of molecules from solution encompasses a number of key areas in science and technology, ranging from the purification and separation of industrial chemicals through to the arrangement of fragile biomacromolecules in ordered arrays suitable for structural analysis. However, as there are only a small number of techniques suitable for the study of such assemblies, many fundamental aspects governing the crystallization of molecules from solution are still poorly understood. In the studies presented here we have attempted to improve the understanding of this subject by investigating the crystallization of a series of molecules of both pharmaceutical and biological importance, using in situ Atomic Force Microscopy (AFM). A particular aim of the PhD was to develop the experimental protocols necessary to investigate macromolecular crystals known to exhibit poor diffraction properties, and subsequently to relate AFM data to these properties.